Multi criteria decision making to determine the location of Via Laundry's branch - Theodora, Tania; Septiani, Winnie; Dewayana, Triwulandari S (Universitas Mercu Buana, 2024)
Decision of choosing the right business location will determine the future development of the business itself. Location decision making is not only important in terms of costs and profits but is also one part of a company's strategic planning which is significant in increasing competitive advantage. Via Laundry’s owners has decided to open a new store branch to expand their business as it has been well-operated for 3 years. Business owners have determined several alternatives for this new branch’s location, namely Transpark Djuanda Bekasi, Jakarta Garden City, and Harapan Indah. The purpose of this study will help business owners to better decide preferred location for the new branch by using multi-criteria decision making, which is AHP and TOPSIS combined methods. Determination of criteria and alternatives is carried out based on the results of discussions with experts, namely business owners and their business partners. Experts also assess the importance of each criterion to produce a pairwise comparison matrix. Based on the results of calculations using the AHP method, priority vector values are obtained for the 6 criteria from the highest to the lowest weight, namely population density (0.370), water cleanliness (0.249), rental costs (0.131), land area (0.103), ease of access roads (0.093), and competitiveness level (0.054). Calculation using AHP method generate weight of each criterias which is then used in TOPSIS. By comparing the distance with ideal solution, preference value for each alternative can be obtained, namely 0.3053 for Jakarta Garden City, 0.3624 for Harapan Indah, and 0.8009 for Transpark Djuanda Bekasi. The chosen location recommendation for Via Laundry’s new branch is Transpark Djuanda Bekasi with the highest preference value of 0.8009.